THE EFFECTIVENESS OF AR MEDIA BASED ON LOCAL WISDOM ON ELEMENTARY STUDENTS’ CRITICAL THINKING IN MERDEKA CURRICULUM - Khoirul Maula; Misbah Binasdevi; Patimah (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
Critical thinking skills are essential 21st-century key competencies, however they are still low among elementary school students due to the lack of technology integration in learning. The merdeka curriculum encourages the use of technology to create contextual learning experiences. This study aims to test the effectiveness of local wisdom-based Augmented Reality (AR) media in improving the critical thinking skills of fourth-grade students at SDN Tenajar Kidul II, Indramayu Regency. The method used was quantitative with a one-group pretest-posttest design. The results showed a significant increase in students' critical thinking skills after using AR media, with a moderate increase category. These findings conclude that locally wisdom-based AR media is effective in improving students' critical thinking skills when implemented within the merdeka curriculum. The implications of this study suggest the need to integrate local content-based AR technology as an innovative alternative to support the development of critical thinking skills.